Adherence to an antioxidant diet and lifestyle is associated with reduced risk of cardiovascular disease and mortality among adults with nonalcoholic fatty liver disease: evidence from NHANES 1999–2018 - Li, Yingzi; Liu, Yipin (Frontiers in Nutrition, 2024)
Background: Nonalcoholic fatty liver disease (NAFLD) stands a prevalent chronic liver condition significantly influenced by oxidative stress. We investigated the unclear relationship between an antioxidant-rich diet and lifestyle and cardiovascular disease (CVD) prevalence rate and mortality in adult patients with NAFLD.Methods: This study utilized data from the National Health and Nutrition Examination Survey (NHAENS) spanning from 1999 to 2018 to investigate the association between adherence to an antioxidant-rich diet and lifestyle and the cardiovascular disease (CVD) prevalence rate and mortality in adult patients with NAFLD. The study employed the Oxidative Balance Score (OBS) to define antioxidant diet and lifestyle. Results: Including 8670 adult patients with NAFLD, the study revealed an inverse association between OBS and the prevalence of most CVD conditions. Fully adjusted models demonstrated that each unit increase in diet OBS, lifestyle OBS, and overall OBS corresponded to a 2%, 7%, and 2% reduction in all-cause mortality, respectively. In model 2, findings revealed that lifestyle Q2 and Q3 were linked to reduced cancer mortality, whereas diet and overall OBS did not exhibit an association. Additionally, Stratified analysis revealed that age (<45 years) and education level (> high school) significantly influenced the association between the OBS and the prevalence of CVD.Conclusions: These results underscore the protective link between adherence to an antioxidant diet and lifestyle and a diminished prevalence of CVD and mortality in adults with NAFLD, particularly among younger and higher-educated populations.